Influence of cold rolling on in vitro cytotoxicity and electrochemical behaviour of an Fe-Mn-C biodegradable alloy in physiological solutions. Issue 11 (November 2018) - Caligari Conti, Malcolm; Aquilina, Daniel; Paternoster, Carlo; Vella, Daniel; Sinagra, Emmanuel; Mantovani, Diego; Cassar, Glenn; Schembri Wismayer, Pierre; Buhagiar, Joseph
Abstract: The properties of cold-worked Fe-13Mn-1.2C steel, as candidate material for scaffolding and stenting applications, have been investigated. The study of the electrochemical corrosion susceptibility of Fe-13Mn-1.2C alloy in protein bearing and non-protein bearing physiological solutions, revealed that there were no differences between the as-received, 10% and 20% cold worked Fe-13Mn-1.2C samples. Although protein addition reduces the overall corrosion rate in static immersion degradation tests for both the cold worked and non-cold worked alloys, there were no discernible differences in the corrosion rates of samples with different percentages of cold work deformations. Similarly, potentiodynamic testing showed no differences between the corrosion rates in solutions with and without protein addition. Atomic absorption spectroscopy (AAS) results—post static immersion—showed similar values of Fe and Mn concentrations in the electrolyte for all the investigated conditions. Cold working was found to increase Grain Average Misorientation (GAM) and deformation twins within the steel, and, consequently, this led to an increase in the elastic modulus. Hence, cold-rolling may be used to achieve smaller sections (volumes) in order to support the equivalent load of the non-cold worked counterpart, giving a larger surface area to the volume ratio, thereby increasing the corrosion rate, and, in turn, rendering the degradation process shorter. When considering cytocompatibility in vitro, the collected supernatant particulate free Fe-13Mn-1.2C steel electrolytes were seen to be equally cytocompatible with no differences being observed between the different percentage cold work conditions. The presence of solid 80 μm size particles in the seeded elutions were seen to change the results and render the Fe-13Mn-1.2C steel non-cytocompatible.